Student absenteeism and the role of police encounters - Geller, Amanda (Criminology & public policy, 2022)
Research Summary Using data from the Fragile Families and Child Wellbeing Study, we estimated associations between adolescent-police contact and several measures of school absenteeism. Adolescents self-reported absences due to health and due to truancy; police contact was linked to both. Youth reporting police contact were absent approximately 2.2 more days in total than those not reporting contact. Police contact was also associated with a 10 percentage point increase in the probability that absenteeism concerns precipitated a parent-teacher conversation. Policy Implications Extensive literature documents a "school to prison pipeline" in which aggressive school discipline exposes students to law enforcement. Less attention has been paid to how police contact outside of school shapes educational experiences. Recognizing and excusing absenteeism driven by police contact can provide students with flexibility needed to maintain educational progress. Such a policy may also signal to students stopped by police that school personnel can serve as sources of support and facilitate linkages to outside resources.